2012
DOI: 10.1111/j.1749-6632.2012.06824.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting plasma cells with proteasome inhibitors: possible roles in treating myasthenia gravis?

Abstract: Myasthenia gravis (MG) is treated primarily with broad-spectrum immuno-suppressants such as prednisone or azathioprine, which normally require several months to reduce autoantibody titers significantly. This delay may be caused by the resistance of the main antibody-producing cells, the plasma cells, to these drugs. In particular, long-lived plasma cells are resistant to immunosuppressive treatments and can produce (auto-) antibodies for months. Bortezomib is a proteasome inhibitor approved for treating patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 74 publications
0
31
0
1
Order By: Relevance
“…Most serum autoantibodies to AChR are produced by long-lived plasma cells residing in spleen and bone marrow. These terminally differentiated cells are resistant to most non-specific immunosuppressive drugs, resulting in a delay of up to 18 months after initiation of general immunosuppressive therapy before MG patients improve [23,24]. Apoptosis of plasma cells can be induced by crosslinking FcgRIIB on the plasma cells by immune complexes [101].…”
Section: Mechanisms Of Specific Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Most serum autoantibodies to AChR are produced by long-lived plasma cells residing in spleen and bone marrow. These terminally differentiated cells are resistant to most non-specific immunosuppressive drugs, resulting in a delay of up to 18 months after initiation of general immunosuppressive therapy before MG patients improve [23,24]. Apoptosis of plasma cells can be induced by crosslinking FcgRIIB on the plasma cells by immune complexes [101].…”
Section: Mechanisms Of Specific Immunotherapymentioning
confidence: 99%
“…Results of a multicenter, randomized, controlled thymectomy trial are eagerly awaited [22]. Nonspecific immunosuppressive drugs mainly suppress lymphocyte activation and proliferation with little effect on long-lived plasma cells that are terminally differentiated cells and continue producing pathogenic antibodies [23,24]. Hence, the use of these drugs is hampered by delayed clinical response and undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In hosts with preexisting humoral immune responses these regimens are slow acting and are only partially capable of depleting NAb levels. This is because NAbs are made mostly by long-lived plasma cells that do not divide, therefore immune suppressants that target proliferating cells are ineffective (8). Furthermore plasma cells lack common B-cell markers making them resistant to anti-CD20 targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have been conducted studying off-label uses of bortezomib. Some studies for the prevention of antibody-mediated rejection in renal transplant patients reported encouraging results, and there are also reports of positive outcomes in the treatment of autoimmune hemolytic anemia, rheumatoid arthritis, and systemic lupus erythematosus (8). …”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting proteolysis, bortezomib disrupts several signal cascades, ultimately resulting in cell death. These effects are most relevant in plasma cells actively producing immunoglobulins and lead to a rapid reduction in Abs synthesis in patients with autoimmune diseases [112]. Bortezomib was effective in several refractory cases of anti-NMDAR encephalitis [51,52].…”
mentioning
confidence: 99%